(untitled) (The Pretoria Student Law Review, 2021)
The focus of this paper will be how linguicide is used as a mechanism to perpetuate epistemic violence in South Africa and how epistemic diversity is needed in order for those who find themselves ‘below the law’ to ascertain access to justice. Firstly, I will define the concepts ‘linguicide’ and ‘epistemic violence.’ Secondly, I will offer a critique on how the English language is not neutral but rather a socioeconomic tool that shapes power relations within society. Thirdly, I will introduce the critical theories of Black Consciousness and Marxism to show how the law is complicit in perpetuating racial and class inequalities in South Africa. I will then conclude with how access to justice can become a reality through the paradigm of decolonisation (‘of the mind’) as understood by various African authors and provide recommendations of an imagined alternative.